PENGGUNAAN MODEL SEARCH, SOLVE, CREATE, AND SHARE (SSCS) DALAM PEMBELAJARAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS V SEKOLAH DASAR DI KECAMATAN SUMEDANG UTARA - Sri Rezeki, Neneng; Saepurokhman, Asep; Budiman, Arip (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Writing descriptive text is the art of depicting or describing an object or phenomenon in vivid detail, with the primary goal of conveying the author's experience to the reader. This means the writer acts as the reader's "eyes," observing visual details directly and then translating them into words. More than simply informing, the writer strives to stimulate the reader's imagination and senses, so they can see, hear, or feel the object being described for themselves, even if they have never witnessed it in person. Based on field observations, students experience difficulty developing ideas or concepts, lack attractive designs, and lack writing skills. This is due to the lack of variety in the learning models implemented by teachers. This study aims to describe the learning outcomes of writing descriptive text using the Search, Solve, Create, and Share (SSCS) learning model for fifth-grade elementary school students in North Sumedang District, Sumedang Regency, in the 2025/2026 academic year. Therefore, the instruments used were teaching modules, observation sheets, tests, and student learning motivation questionnaires. The method used in this study was a quasi-experimental approach with qualitative and quantitative analysis. Based on data analysis, the success rate of poster writing learning using the SSCS model in the three sample classes is categorized as high. This is evidenced by the z-test calculation results, which show a calculated Z of -0.51, while the z-table for a 1% significance level is 2.33. Comparing the calculated Z values, it is found that the calculated Z values ​​lie within the range of -z to z. Because the calculated Z values ​​lie within the range of -z0.4900 to z0.4900 (-2.33 < -0.51 < 2.33), the hypothesis proposed in this study is accepted. Thus, the learning outcomes of poetry writing using the Search, Solve, Create, and Share (SSCS) learning model for fifth-grade elementary school students in North Sumedang District in the 2025/2026 academic year are categorized as high.